Does Supply Chain Participation Influence SME Demand Expectations During Market Turbulence? An Exploratory Study - Garbelli, Maria (European Scientific Journal, ESJ, 2026)
Small and medium-sized enterprises (SMEs) represent a cornerstone of the Italian industrial system, particularly within strategic supply chains (SSC) that are increasingly regarded as critical to resilience and competitiveness. However, existing literature suggests that the benefits of supply chain integration may not be unequivocal, especially under conditions of heightened market turbulence. This paper investigates whether participation in a strategic supply chain enhances or constrains SME performance and short-term expectations in uncertain economic environments. The analysis is based on qualitative survey data collected from SMEs in Lombardy, Italy’s most industrialized region. The study compares two groups: firms affiliated with at least one strategic supply chain and firms operating independently. The empirical assessment focuses on structural characteristics, strategic positioning, and short-term demand expectations, highlighting differences in perceived adaptability and outlook between the two groups. The findings contribute to the debate on inter-firm cooperation by identifying both the advantages and potential trade-offs associated with structured supply chain participation, particularly in contexts characterized by economic instability and environmental turbulence.